KORELASI ANTARA PEMBAJARAN AL-QUR’AN METODE WAFA DENGAN PRESTASI BELAJAR QUR’AN HADIS SISWA MI NURUL HUDA GROGOL - Lina Eka Khoiriyah; Happy Susanto; Nurul Abidin (TARBAWI:Journal on Islamic Education, 2018)
The learning of al-Qur'an in the WAFA method is a method that prioritizes the right brain, is comprehensive, enjoys enjoyment so that it accidentally gets meaningful lessons, and the delivery of the material includes three modalities namely visual, auditory, and kinesthetic. Besides that interesting learning is accompanied by the rhythm of songs, movements, claps, and imagination. The WAFA method uses Hijaz tones so students are easily accepted and remembered. Through this form of delivery, students are excited. The writing of this thesis aims to describe: 1) Knowing the implementation of the Al-Qur'an learning method of Wafa in MI Nurul Huda Grogol. 2) Knowing students 'learning achievement in the Hadith Qur'an field in MI Nurul Huda Grogol 3) Knowing the correlation between the Al-Qur'an learning method of Wafa on students' learning achievement in the Hadith Qur'an study in MI Nurul Huda Grogol. This research is a quantitative research with data processing using SPSS 18 Product Moment Correlation. Data collection techniques carried out are observation, interview, and questionnaire techniques. Furthermore, the data is obtained, test hypotheses, discussions, and conclusions. The findings of this thesis research prove that: 1) The implementation of the Al-Qur'an learning method of WAFA carried out in MI Nurul Huda Grogol is very pleasant. 2) Students get satisfactory learning achievements during the Hadith Qur'an evaluation both daily, memorizing, group assignments, and semester tests. Students can answer the teacher's questions spontaneously correctly and just before the lesson begins. 3) There is a correlation between the learning of the Qur'an and the WAFA method with learning achievements in the field of Qur'an study. 0.012 and variable Y 0.012, and the percentage correlation value was 32.4%